Usefulness of the theory of planned behavior to understand the consumption of fruits and vegetables: evidence of studies on Chilean adults and adolescents - Peña-y-Lillo, Macarena Sofia (Revista Española de Comunicación en Salud, 2019)
Introduction: The theory of planned behavior (TPB) proposes that human behavior can be explained as a function of intentions to perform a given behavior, which in turn are determined by attitudes, normative perceptions and perceptions of control. The model has been extensively recommended and utilized to guide the design of public health communication interventions. Goals: The purpose of this work is to explore the associations of the TPB constructs in the context of fruit and vegetable consumption in the Chilean population. Methods: Two quantitative studies with a descriptive non-experimental design were conducted. The first corresponds to a face-to-face cross-sectional survey of adults 18 to 78 years of medium and low socioeconomic status (N = 250). The second corresponds to a longitudinal self-applied survey of female adolescents 12 to 18 years old (N = 751). The data were analyzed using multiple and hierarchical regressions. Results: In both studies, it was found that attitudes, norms and perceptions of control were significantly associated with intentions. Intentions, in turn, had a cross-sectional association with behavior. Conclusion: This study’s findings underscore the usefulness of the TPB to guide interventions aimed at promoting healthy eating, especially the importance of attitudes and perceptions of control for this purpose.